Vicente Krause - De Grandis, María Belén; Instituto de Investigación en Historia Teoría y Praxis de la Arquitectura y la Ciudad (HiTePAC). Facultad de Arquitectura y Urbanismo (FAU). Universidad Nacional de La Plata (UNLP). Calle 47, N° 162 (1900) La Plata (Instituto de Arte Americano e Investigaciones Estéticas “Mario J. Buschiazzo”, 2019)
During the 1960s, the performance of the first generation of architects graduated in the Universidad Nacional de La Plata renewed the architectural landscape of the city. The figure of Vicente Krause emerges among its representatives. He could join artistic sensitivity with technical knowledge in his design experimentation, through his own poetic. This article is proposed as a contribution to the analysis of his work from a biographical perspective focused on his relationship with art. It also intents to dismantle the personalist image shaped by the  architect, to place him in the ideas of that time, his collective path and the different faces of his production, in an economical and political changing context. The study about his legacy seeks to reassess his trajectory, jointly with the role of other referents that worked in the local field and went unnoticed in the 20th Century argentinian historiography.